Pelatihan Bahasa Asing di SMKN 1 Temon Kulonprogo - Yuni Wachid Asrori; Erlin Estiana Yuanti; Mery Kharismawati; Supriadianto Supriadianto; Nur Endah Nugraheni; Th. A. Rencidiptya G.F; Wahyu Kartika Wienanda; Rekno Irawati; Andri Hermawan (Jurnal Pengabdian dan Pengembangan Masyarakat, 2021)
This community service was conducted by considering Kulonprogo Regency’s development. Massive physical development in Kulonprogo Regency should be balanced with the human resources improvement. Foreign languages skill was chosen to be improved because Kulonprogo Regency’s community will be intensively interact with foreigners due to the existence of new airport (New Yogyakarta International Airport). Foreign languages training focused on the English, Korean and Japanese was given to the students of Vocational Senior High School in Temon (SMK N 1 Temon) which has specialty in marine and sailing. Teaching materials were prepared by conducting an interview with the teachers to find the need based on the curricullum competency. Based on the findings, community service team composed and compiled teaching materials. The team also delivered the materials through classroom teaching in several classes of SMK N 1 Temon. Through this program, foreign languages training on English, Korean and Japanese has been optimally received by SMK N 1 Temon students.